PENGARUH DRIVE FOR ENVIRONMENTAL RESPONSIBILITY, COLLECTIVISM DAN SUBJECTIVE NORM TERHADAP BEHAVIORAL INTENTION PENGGUNAAN REUSABLE BAG - Ayu Ekasari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
The purpose of the research is to examine the effect of driver for environmental responsibility, collectivism and subjective norm on behavioral intention in using reusable bag. This was a quantitative survey using a total sample of 282 respondents. Data were analyzed by using multiple regression method in order to test the hypotheses. Findings of the research revealed that driver for environmental responsibility and subjective norm were two strong predictors for behavioral intention in using reusable bag. However, there was no significant effect of collectivism on behavioral intention. The study contributes to the literature of pro-environmental behavior and its antecedents as well as suggestions for policy makers and retailers to design effective social marketing campaign to promote pro-environmental behavior, which is using reusable bag.